2014
DOI: 10.1038/bjc.2014.360
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cell-free cancer-testis MAGE-A RNA, BORIS RNA, let-7b and miR-202 in the blood of patients with breast cancer and benign breast diseases

Abstract: Background:MAGE-A (melanoma-associated antigen-A) are promising targets for specific immunotherapy and their expression may be induced by the epigenetic factor BORIS.Methods:To determine their relevance for breast cancer, we quantified the levels of MAGE-A1, -A2, -A3, -A12 and BORIS mRNA, as well as microRNAs let-7b and miR-202 in pre- and postoperative serum of 102 and 34 breast cancer patients, respectively, and in serum of 26 patients with benign breast diseases and 37 healthy women by real-time PCR. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 37 publications
(46 reference statements)
4
60
0
Order By: Relevance
“…In human ESCCs, miR-202 regulated apoptosis by targeting HSF2 via mechanism involving caspase-3. A study also identified that miR-202 plays an important role in regulating cell proliferation, migration and invasion of cervical cancer (CC) by directly targeting cyclin D1, and miR-202 may represent a potential therapeutic target for patients with CC (16)(17)(18)(19)(20)(21)(22). In addition, a previous study showed that an increased serum concentration of miR-202 may be a strong independent prognostic factor for breast cancer patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…In human ESCCs, miR-202 regulated apoptosis by targeting HSF2 via mechanism involving caspase-3. A study also identified that miR-202 plays an important role in regulating cell proliferation, migration and invasion of cervical cancer (CC) by directly targeting cyclin D1, and miR-202 may represent a potential therapeutic target for patients with CC (16)(17)(18)(19)(20)(21)(22). In addition, a previous study showed that an increased serum concentration of miR-202 may be a strong independent prognostic factor for breast cancer patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, exploring the profiles of miRNAs and their target genes involved in tumorigenesis may promote understanding of the underlying mechanisms of patients with human malignancies, and provide valuable insight for the early diagnosis and treatment of such diseases (2022,24). Results from previous studies have continually demonstrated that the presence of miRNAs in the circulation and in bodily fluid may function as promising diagnostic and prognostic biomarkers in certain diseases, including human malignancies (2325,29). …”
Section: Discussionmentioning
confidence: 99%
“…Further studies have shown that the circulating miRNA profile reflects disease states, particularly in cancer (24,25). However, the association between miRNA profiles in circulation and in tumor tissues remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One other SNP located in miR-202 (rs12355840) was found to be associated with breast cancer in stage 1 of our study (OR = 0.78, P = 0.005), but not in the stage 2 replication (OR = 0.94, P = 0.27), with the pooled result (OR meta = 0.90, P = 0.02). This particular SNP and miR-202 were found to be associated with breast cancer risk and prognosis in several other studies, indicating a potential functional role of this miRNA, and warranting further studying of this miRNA in breast cancer diagnosis, prevention, and treatment (Joosse et al 2014; Rawlings-Goss et al 2014; Schrauder et al 2012). …”
Section: Discussionmentioning
confidence: 68%